The challenge of effective speaking - Verderber, Rudolph F.; Sellnow, Deanna D.; Verderber, Kathleen S. , 1949- (Boston, Massachusetts : Wadsworth Cengage Learning, 2012)
Do you want to ace your public speaking course? All you need to know, including all of the skills that will help you become a confident speaker and conquer speaking anxiety, are thoroughly covered in THE CHALLENGE OF EFFECTIVE SPEAKING, 15e. A favorite with students, this best seller guides you through six key "Speech Planning Action Steps." The result? You'll learn how to prepare and deliver strong speeches that get you good grades in your public speaking course! You'll be guided through topic selection, audience analysis and adaptation, effective research (including appropriate use of Internet resources), organization (with an emphasis on outlining), and language and delivery. The new 15th edition of this nationwide best seller also including many online tools, including videos of actual student speeches accompanied by Interactive Video Activities that help you develop and strengthen your public speaking skills. Authors Rudy and Kathie Verderber, together with new coauthor Deanna D. Sellnow, have grounded this new edition with the latest research to give you an exceptional resource for creating and delivering your speeches
1. Orientation -- 2. Principles -- 3. Informative and persuasive speaking -- 4. Adapting to other occasions and formats
Includes bibliographical references (p. 362-366) and index
Keywords: Public speaking